Review of the Marriage Age Limit Policy in Indonesia Through the Saad al-Dzari'ah Principles - Jamaluddin Bin Hashim; Su’udin Aziz (Indonesian Journal of Islamic Law, 2023)
This research examines the latest policy regarding the age limit for marriage in Indonesia, which sets a minimum age of 19 years for both sexes. The main objective is to assess the impact and effectiveness of this policy in the context of social, health and gender equality, through the lens of Saad al- Dzari'ah principles which are oriented towards preventing social damage before it occurs. The methodology used includes a juridical-normative approach with statistical data analysis, case studies, and in-depth interviews with various stakeholders. The results showed a significant reduction in early marriage, an increase in education and economic preparedness, and a reduction in reproductive health risks. This study also identified that the application of Saad al-Dzari'ah principles has been effective in preventing social problems related to early marriage and supporting gender equality. Policy recommendations include increasing the minimum marriage age, broader educational campaigns, integration of religious values in public policy, and regular monitoring and evaluation. This research provides valuable insights for policy makers in formulating marriage regulations that are responsive to ongoing social dynamics, while respecting the juridical, social and religious values of Indonesian society.